2019
DOI: 10.1186/s13568-018-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid production by a gamma ray-induced Pseudomonas aeruginosa mutant under solid state fermentation

Abstract: Solid-state fermentation has a special advantage of preventing the foaming problem that obstructs submerged fermentation processes for rhamnolipid production. In the present work, a 50:50 mixture of sugarcane bagasse and sunflower seed meal was selected as the optimum substrate for rhamnolipid production using a Pseudomonas aeruginosa mutant 15GR and an impregnating solution including 5% v/v glycerol. Using Box–Behnken design, the optimum fermentation conditions were found to be an inoculum size 1% v/v, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 40 publications
(47 reference statements)
0
13
1
Order By: Relevance
“…Partial sequencing of the 16S rRNA gene in combination with the biochemical tests results enabled the confirmation of the identity of the strain as P. aeruginosa. This species is considered a metabolically versatile bacterium that is able to use a variety of simple and complex carbon sources and can survive under normal and harsh environmental conditions (Rojo 2010 ; El-Housseiny et al 2019 ). These characteristics make P. aeruginosa an excellent candidate for rhamnolipid production using unusual carbon sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial sequencing of the 16S rRNA gene in combination with the biochemical tests results enabled the confirmation of the identity of the strain as P. aeruginosa. This species is considered a metabolically versatile bacterium that is able to use a variety of simple and complex carbon sources and can survive under normal and harsh environmental conditions (Rojo 2010 ; El-Housseiny et al 2019 ). These characteristics make P. aeruginosa an excellent candidate for rhamnolipid production using unusual carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compared to water-soluble carbon sources (e.g., glucose), the use of water-insoluble carbon such as vegetable oil generally produces rhamnolipids in higher titers (Chong and Li 2017 ). The use of factorial design to optimize culture conditions has been proven to be a successful approach to significantly increase the rhamnolipid yield obtained using several P. aeruginosa strains (Camilios-Neto et al 2008 ; Kumar et al 2015 ; Ozdal et al 2017 ; El-Housseiny et al 2019 ). Various studies (see Table 1 ) have explored economical production methods using low-cost and readily available nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reached yield and productivity of 0.21 g g −1 and 0.58 g L −1 h −1 , which, however, are low when compared to traditional production systems. Other biosurfactants produced by SSF are rhamnolipids (El-Housseiny et al, 2019). Productivities of 0.19 g L −1 h −1 were obtained using agroindustrial residues as substrates and Pseudomonas aeruginosa as inoculum.…”
Section: Product Developmentmentioning
confidence: 99%
“…As with the sophorolipids, the productivities are lower than those observed in traditional production systems. However, it is expected that by devoting more effort to SSF optimization, both reactor design and control parameters, further improvements can be reached (Wang et al, 2018;El-Housseiny et al, 2019). Jimenez-Peñalver et al 2018also reported that there is a high influence of the substrates on the type and yield of sophorolipid produced.…”
Section: Product Developmentmentioning
confidence: 99%
“…Several bacterial genera have been reported as biosurfactant producers, for example, Acinetobacter, Arthrobacter, Pseudomonas, Halomonas, Bacillus, Rhodococcus, Enterobacter, Serratia [5] [6] [7] [8], and fungal species such as Saccharomyces cerevisiae [9], Fusarium fujikuroi [10], Candida tropicalis [11], Pseudozyma [12], Xylaria regalis [13]. Pseudomonas aeruginosa strains are among the effective producers of biosurfactant [14] [15].…”
Section: Introductionmentioning
confidence: 99%